ADDITION OF BETAINE IN DRINKING WATER REDUCE MORBIDITY AND MORTALITY OF BROILER - Rohmandhani, Roby; Ardana, Ida Bagus Komang; Suharsono, Hamong (Buletin Veteriner Udayana, 2021)
Heat stress in broiler can trigger the emergence of various diseases, affect immune function, increased morbidity and mortality rates. This study aims to determine the effect of betaine with different doses in drinking water on morbidity and mortality. The sample of this study amounted to 1,200 female broilers in the Heri Farm poultry, Palaran Samarinda. The design used in this study was Randomized Block Design (RBD) with 4 treatments, P0 (0.0 g/L), P1 (0.5 g/L), P2 (1.0 g/L) dan P3 (2.0 g/L). Morbidity and mortality data were analyzed by Univariate analysis and continued with the Duncan test if the significant difference is (P <0.05). The results showed that the addition of betaine had a significant effect (P <0.05) on reducing mobility and mortality rates. The addition of betaine with 1.0 g/L is the best dose to reduce broiler morbidity and mortality rates, respectively 5.66% and 5.67% toward the controls.